2021
DOI: 10.1002/advs.202101019
|View full text |Cite
|
Sign up to set email alerts
|

Sandwiched Cathodes Assembled from CoS2‐Modified Carbon Clothes for High‐Performance Lithium‐Sulfur Batteries

Abstract: Structural design of advanced cathodes is a promising strategy to suppress the shuttle effect for lithium‐sulfur batteries (LSBs). In this work, the carbon cloth covered with CoS2 nanoparticles (CC‐CoS2) is prepared to function as both three‐dimensional (3D) current collector and physicochemical barrier to retard migration of soluble lithium polysulfides. On the one hand, the CC‐CoS2 film works as a robust 3D current collector and host with high conductivity, high sulfur loading, and high capability of capturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 77 publications
(91 reference statements)
1
44
0
Order By: Relevance
“…Considering the favorable catalytic properties of CoS 2 , a sandwiched cathode composed of carbon clothes modified by CoS 2 was designed. 116 It confirms from theoretical simulations that large negative Gibbs free energy on the surface of cathodes is responsible for the high catalytic activity (Figure 8C). Su et al also employed theoretical models to explain the improved reaction thermodynamics by the Fe 3 O 4 /CNSs-PP separator as well.…”
Section: Srr Modelsupporting
confidence: 79%
“…Considering the favorable catalytic properties of CoS 2 , a sandwiched cathode composed of carbon clothes modified by CoS 2 was designed. 116 It confirms from theoretical simulations that large negative Gibbs free energy on the surface of cathodes is responsible for the high catalytic activity (Figure 8C). Su et al also employed theoretical models to explain the improved reaction thermodynamics by the Fe 3 O 4 /CNSs-PP separator as well.…”
Section: Srr Modelsupporting
confidence: 79%
“…For the cathodes before charge-discharge cycling, each plot consists of a semicircle at the high frequency related to the charge transfer resistance (R ct ) and an inclined line at the low frequency corresponding to the ion diffusion resistance (R s ). [18] The R ct value of the S/CoS 2 @MMT-10 cathode (29 Ω) is close to that of the S/CoS 2 cathode (25 Ω) and much smaller than that of the S/MMT cathode (162 Ω), indicating that CoS 2 endows the CoS 2 @MMT-10 composite with high electrical conductivity. Thus, the CoS 2 @MMT-10 composite can promote local and overall electron transport in the composite cathodes and improve the sulfur utilization.…”
Section: Chemsuschemmentioning
confidence: 76%
“…Yuan et al investigated the catalysis effect of CoS 2 in promoting the LiPSs redox reactions via micrometer-sized CoS 2 particles for the first time. [13] More recently, CoS 2 with different structures and morphologies were further developed for use in LiÀ S batteries in related works, [14][15][16][17][18] among which CoS 2 was mostly combined with porous carbon materials. It was found that the incorporation of these CoS 2 particles did enhance the reaction kinetics and cycling performance of LiÀ S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2E , the Co 2p 1/2 and Co 2p 3/2 characteristic peaks of CoS 2 were located at 794.4 and 779.4 eV in the HR-XPS of Co 2p, respectively. ( Xu, et al, 2021 ). The satellite peak signal is 781.8, 786.1, 797.5, and 803.4 eV ( Wang, et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%